What Type of Public Capital Contributes to Private Production? - Fumitoshi Mizutani; Tomoyasu Tanaka (European Regional Science Association (ERSA), 2004)
The main purpose of this study is to determine whether public capital contributes to productivity growth and, if so, what kind of public capital contributes most. We analyze a dataset of 46 prefectures in Japan over 41 years, from 1955 to 1995, and estimate the production function as the first-differenced form. In the case where analysis was conducted using aggregate public capital, public capital shows a positive contribution to private production. However, we could find no clear productivity effects when using smaller components of public capital. Key Words: Public Capital, Productivity Effect, Infrastructure, Spill-over Effect JEL: Classification H50, H54, R53
Keywords: H50; H54; R53; 330; Public Capital; Productivity Effect; Infrastructure; Spill-over Effect